2020
DOI: 10.3389/fnins.2020.00930
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of SNHG14 Alleviates MPP+-Induced Injury in the Cell Model of Parkinson’s Disease by Targeting the miR-214-3p/KLF4 Axis

Abstract: Background: Parkinson's disease (PD) is the second most common neurodegenerative disease. Long non-coding RNA (lncRNA) small nucleolar RNA host gene 14 (SNHG14) has been demonstrated as an important regulator in PD pathology. However, the functional mechanisms played by SNHG14 in PD remain largely unclear. Methods: We used 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 1methyl-4-phenylpyridinium (MPP +) to establish PD mouse and cell models. The levels of SNHG14, miR-214-3p, and Krüppel-like factor 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…SNHG14 is detected on chromosome 15q11.2 and functions as an oncogene in cancers, kidney injury, and neurodegenerative diseases such as PD and AD, working as ceRNA (Qi et al, 2017 ; Wang et al, 2018 ; Zhuang et al, 2022 ). It was proved that SNHG14 is up-regulated in two ceRNA regulatory axes, including SNHG14/miR-519a-3p/ATG10 and SNHG14/miR-214-3p/KLF4 (Zhou et al, 2020b ; Zhuang et al, 2022 ). Autophagy-related 10 (ATG10) is an E2-like enzyme involved in the autophagy (Zhang M.-Q.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG14 is detected on chromosome 15q11.2 and functions as an oncogene in cancers, kidney injury, and neurodegenerative diseases such as PD and AD, working as ceRNA (Qi et al, 2017 ; Wang et al, 2018 ; Zhuang et al, 2022 ). It was proved that SNHG14 is up-regulated in two ceRNA regulatory axes, including SNHG14/miR-519a-3p/ATG10 and SNHG14/miR-214-3p/KLF4 (Zhou et al, 2020b ; Zhuang et al, 2022 ). Autophagy-related 10 (ATG10) is an E2-like enzyme involved in the autophagy (Zhang M.-Q.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of miR-214 leads to a decrease in α-synuclein expression, which is a potential mechanism that underlies the neuroprotection in Resveratrol, a potential therapeutic drug in PD treatment. Another study demonstrated that miR-214 targets KLF4 in order to alleviate 1-methyl-4-phenylpyridinium (MPP + )-triggered cytotoxicity in PD (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of PD is normally accompanied by apoptosis and inflammation of nerve cells (Bhattacharyya et al, 2021 ). Two lncRNAs, namely nuclear-enriched abundant transcript 1 (NEAT1) and SNHG gene 14 (SNHG14), were identified to accelerate this progression (Zhou S. et al, 2020 ; Liu et al, 2021 ). The main hallmark of PD is the loss of dopaminergic neurons (DAs) in the substantia nigra, which correlates with typical PD symptoms including resting tremors and bradykinesia (Xin and Liu, 2021 ).…”
Section: How Do the Ncrnas Regulate Parkinson’s Disease?mentioning
confidence: 99%